2022
DOI: 10.1111/cpr.13387
|View full text |Cite
|
Sign up to set email alerts
|

Smurf1 regulates ameloblast polarization by ubiquitination‐mediated degradation of RhoA

Abstract: Cell polarity is essential for ameloblast differentiation and enamel formation. Smurf1 can mediate cell polarization through ubiquitination degradation of specific substrates. But it remains unclear whether Smurf1 could regulate ameloblast polarity and the underlying mechanism. Here, immuno-fluorescence staining and RT-qPCR were applied to detect the expression of Smurf1 and F-actin. A mouse lower incisor defect model was constructed. Scanning electron microscope, rat lower incisor culture, western blot, wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…66 SMURF1 is a significant regulator of RhoA degradation. 67 Rajagopalan et al have reported that enhancing proteasomal function, such as promoting SMURF1-mediated ubiquitination of RhoA, has a partially protective effect on right ventricular hypertrophy and failure. 68 Meanwhile, the hearts of mice with cardiomyocyte-specific RhoA deficiency exhibited a reduced degree of fibrosis in reaction to aortic pressure overload, 69 thereby offering novel perspectives on the treatment of hypertension and cardiac hypertrophy.…”
Section: Hypertension and Cardiac Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation
“…66 SMURF1 is a significant regulator of RhoA degradation. 67 Rajagopalan et al have reported that enhancing proteasomal function, such as promoting SMURF1-mediated ubiquitination of RhoA, has a partially protective effect on right ventricular hypertrophy and failure. 68 Meanwhile, the hearts of mice with cardiomyocyte-specific RhoA deficiency exhibited a reduced degree of fibrosis in reaction to aortic pressure overload, 69 thereby offering novel perspectives on the treatment of hypertension and cardiac hypertrophy.…”
Section: Hypertension and Cardiac Hypertrophymentioning
confidence: 99%
“…Treatment with RhoA inhibitors has been shown to have positive effects on blood pressure reduction and cardiac hypertrophy recovery 66 . SMURF1 is a significant regulator of RhoA degradation 67 . Rajagopalan et al have reported that enhancing proteasomal function, such as promoting SMURF1‐mediated ubiquitination of RhoA, has a partially protective effect on right ventricular hypertrophy and failure 68 .…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%